Martes americana subsp. americana Turton 1806 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Martes americana subsp. americana Turton 1806 Martes americana subsp. americana Turton 1806, in: Linnaeus, Gen. Syst. Nat., Vol. 1: 60. Type Locality: "North America". Synonyms: Martes americana subsp. huro (F. Cuvier 1823); Martes americana subsp. leucopus (Kuhl 1820); Martes americana subsp. martinus (Ames 1874). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 608, DOI: 10.5281/zenodo.7316519